Integration of Retroviruses: A Fine Balance between Efficiency and Danger - Fischer, Alain (Public Library of Science, 2005)
Since retroviruses can integrate a copy of their DNA into the host cell DNA, they are good vectors for gene therapy. But such vectors also have oncogenic potential